(untitled) (Annual of the Faculty of Philosophy in Skopje, 2017)
The experience and the knowledge of our body is the first layer through which we experience ourselves and we become aware of the world in which we exist. Because of that, the purpose of the research is to examine the basic gnostic functions of the persons with intellectual disabilities regarding the knowledge of parts of their bodies. For that purpose, a research was conducted on a sample of 43 examinees with an intellectual disability (ID). The scale for assessment of knowledge of body parts by Stevanovic, Bojanin and Dajin (1992) was used. The research hypotheses showed a better understanding of the body parts by the male examinees, the examinees from rural settings and the examinees on a younger age. The persons with multiple disabilities have a smaller knowledge of the body parts in comparison to the group with ID. In general, the results show weaker knowledge of the body parts in the examinees with intellectual disabilities which are not in accordance with their chronological age.